2004
DOI: 10.1097/01.ccm.0000134404.63292.71
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of procalcitonin and calcitonin gene-related peptide by adherent monocytes and by macrophage-activated adipocytes*

Abstract: The adhesion-induced, transient expression and secretion of procalcitonin and CGRP in vitro may play an important role during monocyte adhesion and migration in vivo. PBMC-derived macrophages may contribute to the marked increase in circulating procalcitonin by recruiting parenchymal cells within the infected tissue, as exemplified with adipocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
179
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(198 citation statements)
references
References 29 publications
6
179
0
13
Order By: Relevance
“…Identifying the peripheral function of these components is complex, because the peptide and its receptor are present both in intrinsic and extrinsic primary sensory afferent neurons (10,11). Moreover, CGRP is produced by and activates migratory cells such as lymphocytes, granulocytes, and monocytes (12)(13)(14). Receptors for CGRP may be induced by intestinal inflammation, as is the substance P neurokinin 1 receptor in T cells and in intestinal epithelial cells (3,15).…”
mentioning
confidence: 99%
“…Identifying the peripheral function of these components is complex, because the peptide and its receptor are present both in intrinsic and extrinsic primary sensory afferent neurons (10,11). Moreover, CGRP is produced by and activates migratory cells such as lymphocytes, granulocytes, and monocytes (12)(13)(14). Receptors for CGRP may be induced by intestinal inflammation, as is the substance P neurokinin 1 receptor in T cells and in intestinal epithelial cells (3,15).…”
mentioning
confidence: 99%
“…Indeed, Linscheid et al (15) reported a transient elevation in PCT mRNA expression by human peripheral blood monocytes immediately after adherence to endothelial cells or plastic surfaces. Furthermore, expression of calcitonin or calcitonin gene-related peptide 1 was noted in adipose tissue biopsies but not in leukocytes isolated from patients with high serum levels of PCT (15,38). In coculture experiments, adipocyte calcitonin mRNA expression was stimulated by E. coli-activated macrophages in which calcitonin mRNA was undetectable (15).…”
Section: Discussionmentioning
confidence: 96%
“…Two isoforms of calcitonin gene-related peptide (CGRP), alpha-CGRP and beta-CGRP, are widely expressed in serum. 31,32 To study the selectivity of this assay, we tested the cross-reactivity of PCT to both isoforms of calcitonin; and our assay exhibited a little cross-reactivity, which was acceptable for the analysis.…”
Section: Discussionmentioning
confidence: 99%